Legitimation of Authority through Image and Legend: Seals Belonging to Officials in the Administrative Bureaucracy of the Ur III State - Winter, Irene J.
with three appendices: List of officials by reign of king cited in seal inscriptions. List of titles or offices by reign of cited king. Relationships among seal-holders